Synergistic Development of Cybersecurity and Functional Safety for Smart Electric Vehicles - Siddhesh Pimpale (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The introduction of Smart Electric Vehicles (SEVs) represents an increasingly disruption on automotive area, once integrates advanced computer and communication technologies to highly electrical cars, which come with high performances, environment friendly and user friendly characteristics . But the increasing complexity of SEVs prompted by greater dependence on interconnected systems, autonomous capabilities and electrification, presents new challenges in cybersecurity as well as functional safety. The safety and reliability of such vehicles is paramount, as unsafe or unreliable operation in either case represents an unacceptable risk in terms of the performance of the vehicle and safety of the passenger. This paper investigates the integrated development of cybersecurity and functional safety for SEVs, emphasizing the requirement for the parallel development of these domains as components that are not treated separately. In SEVs, cybersecurity is quite crucial in order to prevent the threats of hacking, data breaches and unauthorized access to vehicle systems. Functional safety ensures that important vehicle functions (braking, steering, battery control, etc.) keep working even if some part fails. This convergence of functional safety issues with cybersecurity issues is becoming more crucial, since a security incident can result in a failure of catastrophic consequences for a functional safety system and, conversely. This paper reports the current state of cybersecurity and functional safety standards for SEVs, highlighting challenges that include the weaknesses of communication networks, the potential security threats of over-the-air updates, and the demand for real-time responsive systems for failure. In this paper we suggest a unified framework that combines cybersecurity measures with functional safety principles, with an aim at providing secure systems in which no danger can arise from the attack while maintaining the primary safety level in SEVs. The approach underlines a multi-layered defense with monitoring, secure authentication as well as a thorough test process addressing safety and security. This article uses case studies and industry practices to illustrate the advantages of taking an integrated approach to cybersecurity and functional safety, which can result in SEVs that are more robust against cyber-attacks and functional failures. Finally, recommendations for future research and development are provided, highlighting the urgent requirement for collaboration between carmakers, regulators, and cybersecurity professionals to guarantee SEVs are some of the safest, secure, and reliable vehicles for the fast-paced automotive industry.